Pengaruh Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian pada PT. Era Permata Sejahtera Jakarta - Khusnul Khotimah; Lady Diana Warpindyastuti (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
The increasingly competitive business world demands companies to be able to implement appropriate marketing strategies to improve consumer purchasing decisions. Price and service quality are important factors that influence consumer behavior in determining purchasing choices. PT Era Permata Sejahtera, as a company engaged in general services, has experienced a decline in profits in recent years, which is thought to be related to pricing policies and the quality of service provided to consumers. Therefore, this study aims to analyze the influence of price and service quality on purchasing decisions at PT Era Permata Sejahtera, both partially and simultaneously. This study uses a quantitative approach with a descriptive method. Data were collected through distributing questionnaires to consumers of PT Era Permata Sejahtera, with a purposive sampling technique. Data analysis was carried out using multiple linear regression with the help of SPSS version 26 software, and equipped with validity tests, reliability tests, t-tests, F-tests, and coefficients of determination. The results of the study indicate that partially, price does not significantly influence consumer purchasing decisions, while service quality has a positive and significant influence. Simultaneously, price and service quality significantly influence consumer purchasing decisions.